2015
DOI: 10.5194/isprsarchives-xl-5-w5-99-2015
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Laser Bathymetry for Documentation of Submerged Archaeological Sites in Shallow Water

Abstract: ABSTRACT:Knowledge of underwater topography is essential to the understanding of the organisation and distribution of archaeological sites along and in water bodies. Special attention has to be paid to intertidal and inshore zones where, due to sea-level rise, coastlines have changed and many former coastal sites are now submerged in shallow water. Mapping the detailed inshore topography is therefore important to reconstruct former coastlines, identify sunken archaeological structures and locate potential form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Several studies show the advantages of multi-wavelength LiDAR data in different applications, such as atmospheric processing [8,9], geological analysis [10], fire detection [11], topographic mapping [12][13][14], map updating [15], and plant monitoring [16,17]. Bakula, (2015) [18] analyzed the accuracies of digital terrain models (DTMs) from Optech Titan and showed that the mean differences among DTM generation from three channels were less than 0.03 m, and the composition of the three intensities could be considered an alternative orthoimage product.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Several studies show the advantages of multi-wavelength LiDAR data in different applications, such as atmospheric processing [8,9], geological analysis [10], fire detection [11], topographic mapping [12][13][14], map updating [15], and plant monitoring [16,17]. Bakula, (2015) [18] analyzed the accuracies of digital terrain models (DTMs) from Optech Titan and showed that the mean differences among DTM generation from three channels were less than 0.03 m, and the composition of the three intensities could be considered an alternative orthoimage product.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Advanced discrete return sensors ALTM-Orion could produce data of enhanced quality, which could represent complex structures of vegetation targets at the level of details. Doneus et al (2015) presented a compilation of recent airborne laser bathymetry scanning systems for documentation of submerged archaeological sites in shallow water. The SHOALS system (Irish and Lillycrop, 1999) employs Lidar technology to remotely measure bathymetry and topography in the coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…However, the planar mapping resolution of ALB is limited by the size of the laser footprint which, in turn, is constrained by eye safety considerations (Guenther et al, 2000;Fernandez et al, 2014;Doneus et al, 2015). Precise capturing of blocks or boulders with a diameter of less than 50 cm is therefore impossible with typical ALB setups.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas coastal mapping is the main application of ALB, state-of-the art sensors also enable surveying of smaller inland water bodies and especially clear gravel-bed rivers (Hilldale and Raff, 2008;Kinzel et al, 2013;Fernandez et al, 2014;Mandlburger et al, 2015a). This was mainly made possible by two facts: (i) the increased measurement rate lead to a much higher sampling density (dozens of points per m 2 ), and (ii) by narrowing the beam divergence the laser footprint diameter on the surface was brought down from 2-5 m to approximately 0.5 m for a standard flying height of 500-600 m above ground/water level (Fernandez et al, 2014;Doneus et al, 2015). With those mission parameters capturing of small to medium rivers (width: 5-25 m, depth: 0-4 m) became feasible.…”
Section: Introductionmentioning
confidence: 99%